Pengungkapan Manajemen Risiko, Kepemilikan Manajerial Dan Kepemilikan Institusional terhadap Nilai Perusahaan Melalui Kinerja Keuangan - Aprilia Indah Mlia Wati Malik; Dwi Yana Amalia Sari Fala; Herman Darwis (BJRM (Bongaya Journal For Research in Management), 2024)
This research aims to examine the direct influence of the variables Risk Management Disclosure, Managerial Ownership and Institutional Ownership on Company Value. And test the indirect influence of the Risk Management Disclosure, Managerial Ownership and Institutional Ownership variables on Company Value through Financial Performance in the Indonesian Banking Industry. The population in this study amounted to 47 banking industries. By using the purposive sampling method, a sample of 8 companies was obtained. The data testing methods used are Panel Data Regression Analysis and Path Analysis. The results of this research indicate that Risk Management Disclosure, Managerial Ownership and Institutional Ownership have a direct effect on Company Value. Then Disclosure of Risk Management and Institutional Ownership indirectly influences Company Value through Financial Performance in the Indonesian Banking Industry. Meanwhile, Managerial Ownership has no effect on Company Value through Financial Performance in the Indonesian banking industry.